Pengaruh Ketebalan Pile Cap Abutmen Jembatan terhadap Distribusi Beban pada Tiang Fondasi - Y Djoko Setiyarto; Julia Olivia Joris (Jurnal Teknik Sipil, 2026)
In determining the load received by each foundation pile, the pile cap is sometimes assumed to behave as a rigid element so that it can distribute the axial load uniformly. In reality, this rigid assumption is not always valid and must first be verified whether the pile cap behaves flexibly or rigidly based on the designed thickness. The following study aims to determine the effect of pile cap thickness on load distribution on foundation piles. The results of this study are based on the finite element method, which models the pile cap on the bridge abutment as a shell element and models the foundation pile as a spring. Pile caps measuring 5 m x 11.5 m with varying thicknesses of 0.9 m, 1.2 m, 1.5 m, 1.8 m, 2.1 m, and 2.4 m were studied for their behavior in distributing the load to the 24 foundation piles. Using SAP2000 software, the results of this study show that pile caps with smaller thicknesses behave more flexibly and produce non-uniform load distribution on the foundation piles. On the other hand, the thicker the pile cap, the more uniform the load distribution on the foundation pile. In this study, a pile cap thickness of 1.8 m can already distribute the load on the foundation piles uniformly. However, the use of a thin pile cap thickness of 0.9 m, which is considered to behave flexibly, can still be used as long as it meets the requirements of SNI 2847:2019, and the capacity of each pile to carry the non-uniform load has been reviewed.